BUDAYA PERDAMAIAN DALAM AL-QUR’AN - Halim, Abd. (UIN Sunan Kalijaga Yogyakarta, 2014)
Peace is a dream of all religions. There is no religion that teaches violence. However, in practice, there are still a lot of tragedies caused by both religious fanaticism and misunderstanding of religion. In this article, the author wanted to examine the ethics of peace in the Qur'an. By observing a few verses, although not as a whole, the Qur'an appears to have peace ethics from the smallest scope like a small family up to the most extensive scope of the inter-countries relation.Â